Analysis of the Effectiveness of Avian Influenza Treatment in Humans: Literature Review - Valensia, Rika; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
Avian influenza is an influenza disease that is transmitted from birds, can transmit to humans and then can also be transmitted between humans, so that it can cause epidemics. Avian influenza is caused by a myxovirus virus that belongs to the Orthomyxoviridae family. This disease can be treated with antivirals and various other complementary drugs. These variations were then compared with a systematic literature review method to see which treatment had the best effect on treating avian influenza. The sample used in the research was taken from the population or individuals (case study). Results: most patients were treated with oseltamivir, some were given other antivirals and other additional treatments. Conclusion: treatment using the antiviral oseltamivir given ≤ 2 days after the onset of symptoms showed better treatment effectiveness than using other antivirals and corticosteroids.